Women's land rights in Ethiopia: supporting land degradation neutrality - Roberts, Beth; Brown, Jennifer (Gender and development, 2025)
Emerging evidence and growing global consensus in policy and advocacy spaces increasingly link secure and gender-equitable land tenure rights to more effective, just, and efficient action to address the urgent desertification, land degradation, and drought (DLDD) crisis. However, both women's rights to land and efforts to combat DLDD are complex, requiring both conceptual and practical integration. This submission provides an overview of the conceptual links, detailing available evidence on the relationship between women's land tenure security and land restoration initiatives that aim for land degradation neutrality (LDN). LDN means maintaining a stable or increasing amount and quality of land resources necessary to support ecosystem services and food security. It is the overarching aim of the United Nations Convention to Combat Desertification. Ethiopia is provided as a detailed country case study to provide a practical national-level example for how strengthening women's land rights can and should be integrated into efforts to support LDN. The paper closes by providing recommendations applicable to the Ethiopian context and beyond to guide duty-bearers and practitioners around the globe in their efforts to leverage women's land rights as a means to support LDN.